Numerical optimization of warm hydromechanical deep drawing process parameters and its experimental verification. (September 2020) - Türköz, Mevlüt; Cora, Ömer Necati; Gedikli, Hasan; Dilmeç, Murat; Halkacı, Hüseyin Selçuk; Koç, Muammer
Abstract: Warm Hydromechanical Deep Drawing (WHDD) is considered as an effective sheet metal forming process to overcome low formability problems of lightweight materials, such as aluminum and magnesium alloys, at room temperature. WHDD process combines the advantages of Hydromechanical Deep Drawing (HDD) and Warm Deep Drawing (WDD) processes. In this study, interactive and combined effects of Pressure (P) and Blank Holder Force (BHF) variation on the formability of the AA 5754 aluminum alloy sheets in the WHDD process were investigated experimentally and numerically. Different from available studies, the optimal fluid pressure (P) and blank holder force (BHF) profiles, which were determined numerically using adaptive FEA integrated with fuzzy logic control algorithm (aFEA-FLCA), were validated experimentally for the first time in literature. Consequently, limiting drawing ratios (LDR) of AA5754 material were recorded as 2.5, 2.625, and 3.125 for HDD, WDD, and WHDD processes, respectively. Thus, it was demonstrated that the formability of lightweight materials, such as AA5754, could be increased significantly using the WHDD process through the proposed optimization method. This method was also implemented into the WHDD of an industrial part with complex geometry, successfully forming sharp features with minimal thinning at reduced levels of force, pressure, and time. Consequently, it is reasonably to state that the method developed in this study can be adopted for the manufacturing of any other part using the WHDD process.